Differences in Pain Intensity with Distraction and Relaxation Techniques with Infusation in Childhood 6-12 Year - Saharullah, Saharullah; Syarif, Isymiarni; Saleh, Ariyanti; Erika, Kadek Ayu (Berkala Kedokteran, 2024)
Infusion is a nursing action that is carried out by inserting fluids into the veins for a long time and using an infusion set infusion, an action that is often done in hospitals and has a high risk of anxiety and discomfort. Pain is an unpleasant experience caused by actual or potential tissue damage. Aims: the purpose of this study was to determine the difference in the intensity of pain infusion with distraction and relaxation techniques in children aged 6-12 years at Labuang Baji Hospital Makassar. The type of research used is pre-experimental design: post-test only design, namely by providing intervention/treatment and then seeing the results. researchers provided treatment non farmakologi the form of distraction and relaxation techniques for infusion. The population in this study were 30 child respondents. Collecting data by distributing questionnaires/observations. The analysis of this study used the chi-square test. Infusion is an invasive action that is carried out by inserting fluids into the veins for a long time, an action that is often done in hospitals and has a high risk of anxiety and discomfort. Pain is an unpleasant experience caused by actual or potential tissue damage. There is no significant difference in the effect of pain with distraction techniques and relaxation techniques on children 6-12 years old at Labuan Baji Hospital Makassar with p value = 0.757 greater than = 0.005.